(untitled) (International Conference on Computers in Education, 2017)
This study focused on delineating and utilizing “habit loop” framework: cueing environment, routine, and satisfaction. This study further integrated the habit loop framework into portfolio management game for helping elementary school students to write and rewrite to cultivate good writing habit. According to the habit loop framework, we also proposed two design principles: portfolio visualization and management. The former supports cueing environment; the latter increases satisfaction. Students performed their routines (i.e., writing and rewriting) in a portfolio management game. Briefly, this study creates an environment more conducive to students’ writing to cultivate their consistent habit.